Single-cell profiling of peripheral blood and muscle cells reveals inflammatory features of juvenile dermatomyositis - Chen, Xiangyuan; Lian, Dongsheng; Zeng, Huasong (Frontiers in Cell and Developmental Biology, 2023)
Juvenile dermatomyositis (JDM) is a rare yet serious childhood systemic autoimmune condition that primarily causes skin rashes and inflammatory myopathy of the proximal muscles. Although the associated immune response involves the innate and adaptive arms, a detailed analysis of the pertinent immune cells remains to be performed. Herein, we employ single-cell RNA sequencing combined with bioinformatic analyses to investigate the dynamic changes in cell composition and transcriptional profiles associated with JDM within the peripheral blood and muscle tissues. Analysis of 45,859 cells revealed nine and seven distinct cell subsets in the peripheral blood and muscle tissue, respectively. IFITM2+ and CYP4F3+ monocytes were largely produced, and CD74+ smooth muscle cells (SMCs) and CCL19+ fibroblasts were identified as inflammatory-related cell subtypes in JDM patients, exhibiting patient-specific cell population heterogeneity.The dynamic gene expression patterns presented an enhanced type I interferon response in peripheral blood monocytes and T-cells, and SMCs and fibroblasts in muscle of untreated JDM patients. EGR1 and IRF7 may play central roles in the inflammation in both CD74+ SMCs and CCL19+ fibroblasts, and are considered as potential therapeutic targets for JDM. Moreover, inflammatory-related monocytes could regulate T-cells, and the interaction between immune cells and SMCs or fibroblasts in muscle was enhanced under the inflammatory state. These data provide insights regarding JDM immune dysregulation at the cellular level.